1963
DOI: 10.1037/h0044206
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic susceptibility and MMPI profiles.

Abstract: 4 groups totaling 87 undergraduate females of relatively different hypnotic susceptibility as determined by Form A of the Stanford Scale of Hypnotic Susceptibility completed the questionnaire form of the MMPI. The most susceptible group scored significantly lower than the others on the Pd scale (p<.01), but no other significant differences were found between groups. Mean scores of all susceptibility groups fell within the normal range, suggesting that hypnotic susceptibility is not grossly related to psychopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
1

Year Published

1964
1964
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
2
6
1
1
Order By: Relevance
“…The results of the present study, those reviewed above, and numerous other studies employing such instruments as the Edwards Personal Preference Schedule (Lang & Lazovik, 1962;Rosenhan & Tomkins, in press), the Minnesota Multiphasic Personality Inventory (Faw &Wilcox, 1958;Schulman & London, 1963;Secter, 1961), the California Psychological Inventory (Hilgard & Lauer, 1962;Moore, 1961), and others, lead to a conclusion which has been well expressed by Schulman and London (1963, p.…”
Section: Discussionsupporting
confidence: 77%
“…The results of the present study, those reviewed above, and numerous other studies employing such instruments as the Edwards Personal Preference Schedule (Lang & Lazovik, 1962;Rosenhan & Tomkins, in press), the Minnesota Multiphasic Personality Inventory (Faw &Wilcox, 1958;Schulman & London, 1963;Secter, 1961), the California Psychological Inventory (Hilgard & Lauer, 1962;Moore, 1961), and others, lead to a conclusion which has been well expressed by Schulman and London (1963, p.…”
Section: Discussionsupporting
confidence: 77%
“…There was no evidence that high hypnotizables were more anxious than lows or mediums. Previous studies have also found no association between hypnotizability and general neuroticism (Heilizer, 1960), and some have reported hypnotizability to be associated with greater psychological health (Schulman & London, 1963;Spiegel, Detrick, & Frischholz, 1982;Zlotogorski, Hahnemann, & Wiggs, 1987). The converse hypothesis, that low hypnotizables underreport physical symptoms, is also not supported by the literature (Wickramasekera, 1995).…”
Section: Discussioncontrasting
confidence: 44%
“…The results of the present study, those reviewed above, and numerous others employing such instruments as the Edwards Personal Preference Schedule (Lang & Lazovik, 1962;Rosenhan & Tomkins, 1964), the Minnesota Multiphasic Personality Inventory (Faw & Wilcox, 1958;Schulman & London, 1963;Secter, 1961), the California Psychological Inventory (Hilgard & Lauer, 1962;Moore, 1961), and others, lead to the same conclusion as has been previously expressed by Schulman and London (1963):…”
Section: Discussionsupporting
confidence: 87%